Financial constraints, investments, and environmental strategies: An empirical analysis of judicial barriers. (10th February 2022) - Falavigna, Greta; Ippoliti, Roberto
Abstract: This work analyzes the relation between the judicial system and financial constraints, investigating whether inefficiency in enforcing credit rights can amplify companies' difficulties in collecting resources on the capital market, limiting their access to the funds needed to support investments and environmental sustainability. Considering the Italian manufacturing industry and according to the selected insolvency procedures, our results suggest that, if the time necessary to settle cases decreases by 20%, we can expect an increase in the financial debt ratio between 0.92% and 5.08% and a decrease in the trade credit ratio between 0.81% and 2.71%, as well as an increase in investments between 0.46% and 3.22%. These results are robust under a variety of tests and support the hypothesis that judicial inefficiency represents a barrier to environmental sustainability, preventing investments in key technologies able to support green strategies, as well as the key role of trade dynamics as alternative funding strategy for their business. The economic implications of our evidence could be far‐reaching for the whole economy, not only reducing the competitiveness and financial stability of the national system but also triggering a cascade effect on the market and undermining environmental strategies.